Emission and performance analysis of diesel engine running with CeO2 nanoparticle additive blended into castor oil biodiesel as a substitute fuel - Samuel Tamrat; Venkata Ramayya Ancha; Rajendiran Gopal; Ramesh Babu Nallamothu; Yared Seifu (Scientific Reports, 2024)
Abstract The implications of adding cerium oxide (CeO2) nanoparticles as a fuel additive to a castor oil biodiesel–diesel fuel blend on engine performance and emissions in a single-cylinder four-stroke diesel engine under various speed were examined in the current study. The test fuels used were fossil diesel fuels, B5 blend biodiesel (as 5% biodiesel and 95% diesel), B10 blend biodiesel (as 10% biodiesel and 90% diesel), B15 blend biodiesel (as 15% biodiesel and 85% diesel), B20 blend biodiesel (as 20% biodiesel and 80% diesel), and B25 blend biodiesel (as 25% biodiesel and 75% diesel), with cerium oxide (CeO2) nanoparticle additive (75 ppm). The result of the physio-chemical properties of the oil samples was within the limit of the ASTM standard. The addition of CeO2 nano additive to the biodiesel–diesel blends has demonstrated a significant reduction in emission and increased in engine performance for all biodiesel–diesel blends for the engine operating speed range. From the result B25 have the maximum reduction rate in BSFC and B10 have the minimum reduction rate in BSFC. The average maximum increment of thermal efficiency was 22.2% for B10 with CeO2 inclusion. CO emission increased as engine speed increased. HC emission was reduced for all blend, with and without CeO2 nano additions as speed increased. Maximum NOx emission was seen at the rated speed of 2700 rpm without nano additive and at 2900 rpm with nano additive. CeO2 nano additive reduced the soot opacity by 11.56% for all biodiesel–diesel blends for the engine operating speed range. As the objective of this study the results indicates CeO2 nano additive reduced emissions and improved the performance. So, using sustainable biodiesel–diesel blends made from castor oil with CeO2 nano additive advisable in ideal operating conditions for diesel engines.